1987
DOI: 10.1021/jo00390a019
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization energies and structures of substituted methyl radicals

Abstract: The energies and structures of a large number of substituted methyl radicals and methanes have been calculated at the fully geometry optimized UHF and ROHF 4-31G levels. The radical stabilization energies (RSE's) of the various substituents have been calculated according to the isodesmic reaction X"CHg_" + CH4 -* XnCH4_" + CH3. These RSE's are compared with other radical stabilization scales and with various types of experimental data derived from radical reactions and provide a scale for evaluating the extent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
2
1

Year Published

1991
1991
2009
2009

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(69 citation statements)
references
References 3 publications
4
60
2
1
Order By: Relevance
“…In contrast, eclipsing interactions become more important in longer lived intermediates as a consequence of the slower rate and later transition state, so that more 1,5-trans product is formed. Calculations indicated that the radical stabilization energies of monosubstituted methyl radicals were 2.38 kcal/mol (.CH*OCOH) and 5.30 kcal/mol (.CH20CH3), respectively (26). This order parallels the extent of delocalization of the unpaired electron in related radicals that is reflected by ESR hyperfine splitting constants (27) (RCH20CH2.…”
Section: Resultsmentioning
confidence: 93%
“…In contrast, eclipsing interactions become more important in longer lived intermediates as a consequence of the slower rate and later transition state, so that more 1,5-trans product is formed. Calculations indicated that the radical stabilization energies of monosubstituted methyl radicals were 2.38 kcal/mol (.CH*OCOH) and 5.30 kcal/mol (.CH20CH3), respectively (26). This order parallels the extent of delocalization of the unpaired electron in related radicals that is reflected by ESR hyperfine splitting constants (27) (RCH20CH2.…”
Section: Resultsmentioning
confidence: 93%
“…This attenuation is most likely due to the inductive electron withdrawing ability of these substituents; it is known that an electron-withdrawing group usually plays a duel role in radical stability. [100][101][102][103][104][105] A withdrawing group can stabilize a radical by resonance delocalization (π-withdrawing) and at the same time destabilize the radical by electron induction (σ-withdrawing). Destabilization by electron induction is not surprising due to the electron deficient nature of the oxygen radical center, and can be thought of as an unfavorable "pull-pull" dipole-dipole interaction.…”
Section: -95mentioning
confidence: 99%
“…This is not so surprising because it is well known that HartreeFock (HF) calculations are not able to correctly predict the energies of the systems when bond breaking and bond making activity is involved [2].…”
Section: Resultsmentioning
confidence: 99%